Differences in Vitreous Protein Profiles in Patients With Proliferative Diabetic Retinopathy Before and After Ranibizumab Treatment - She, Xinping; Zou, Chen; Zheng, Zhi (Frontiers in Medicine, 2022)
Proliferative diabetic retinopathy (PDR) accounts for severe impact on vision, its mechanism is still poorly understood. To compare the differences of vitreous protein profiles in PDR patients before and after a complete anti-vascular endothelial growth factor (VEGF) loading dose with ranibizumab treatment. 12 vitreous humor (VH) samples were collected from 6 PDR patients before (set as pre group) and after (set as post group) intravitreal ranibizumab (IVR) treatment. LC–MS/MS and bioinformatics analysis were performed to identify differentially expressed proteins. Proteins were validated with targeted proteomics using parallel reaction monitoring (PRM) in a validation set consisting of samples from the above patients. A total of 2680 vitreous proteins were identified. Differentially expressed proteins were filtrated with fold change ≥2.0 (post group/ pre group protein abundance ratio ≥2 or ≤0.5) and p value less than 0.05 (p <0.05). 11 proteins were up-regulated and 17 proteins were down-regulated, while consistent presence/absence expression profle group contains 1 elevated protein and 9 reduced proteins, among which seven proteins were identified as potential biomarkers for IVR treatment through PRM assays. Bioinformatics analysis indicated the up-regulated proteins were significantly enriched in “GnRH secretion” and “Circadian rhythm” signaling pathway. This report represents the first description of combined label-free quantitative proteomics and PRM analysis of targeted proteins for discovery of different proteins before and after IVR treatment in the same patient. IVR treatment may protect against PDR by promoting SPP1 expression through “GnRH secretion” and “Circadian rhythm” signaling pathway